The Causal Effects of Place on Health and Longevity - Tatyana Deryugina; David Molitor (Institute of Labor Economics (IZA), 2021)
Life expectancy varies substantially across local regions within a country, raising conjectures that place of residence affects health. However, population sorting and other confounders make it difficult to disentangle the effects of place on health from other geographic differences in life expectancy. Recent studies have overcome such challenges to demonstrate that place of residence substantially influences health and mortality. Whether policies that encourage people to move to places that are better for their health or that improve areas that are detrimental to health are desirable depends on the mechanisms behind place effects, yet these mechanisms remain poorly understood.
Keywords: I10; R10; 330; life expectancy; regional variation; place effects